FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU REMAJA PUTERI DALAM MENGHADAPI MENARCHE DI SMP NEGERI 1 DELI TUA TAHUN 2015 - Anita Veronika (Elisabeth Health Jurnal, 2016)
The most crucial thing during the puberty for female teenagers is having the first menstruation or menarche, it becomes the biological signs for sexual maturity. Menarche is the first menstruation for the women that can be the initial for the maturity and healthy women. The purpose of this study is to find out the factors related to female teenagers action in facing the menarche in SMP Negeri 1 Deli Tua. The study method is quantitative approach with Cross sectional method. The damples are 92 people. The results of this study are (1) there is correlation between knowledge and female teenagers action in facing menarche in SMP Negri 1 Deli Tua 2015 with p-value 0,029; (2) there is correlation between behavior and female teenagers action in facing menarche in SMP Negri 1 Deli Tua 2015 with p-value 0,012; (3) there is correlation between family support and female teenagers action in facing menarche in SMP Negri 1 Deli Tua 2015 with p-value 0,000; (4) there is correlation between peers and female teenagers action in facing menarche in SMP Negri 1 Deli Tua 2015 with p-value 0,045; (5) there is correlation between internet and female teenagers action in facing menarche in SMP Negri 1 Deli Tua 2015 with p-value 0,004; (6) the most dominant factor is family support. It is recommended to the family to give support for the female teenagers in preparing the menarche so they can have good sexual reproduction.